PSIKOLOGI PENDIDIKAN DALAM PENDIDIKAN MODERN: ANALISIS LITERATUR TENTANG PENDEKATAN DAN INOVASI - Aep Saepuloh; Eka Supriatna; Loso Judijanto; Muhammad Hendra; Muhammad Sukron Fauzi; Yun Risnawati (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The aim of this research is to explore and understand the application of various educational psychology approaches in the context of modern education and assess the impact of recent innovations on the learning and teaching process. This research aims to analyze various educational psychology theories, such as cognitive, behavioral, and constructivism theories, and evaluate how these theories are applied in current educational practice. The results of this study explain that in modern education, various educational psychology approaches including cognitive, behavioral and constructivism theories provide an important theoretical basis for improving the learning and teaching process. Cognitive theory, developed by Piaget and Vygotsky, emphasizes active experience and social interaction in learning, applied through methods such as project-based learning and scaffolding supported by digital technology. B.F.'s theory of behavior Skinner, with reward systems and gamification, increases student motivation, while constructivism theory is supported by technologies such as AR for immersive learning experiences. The integration of this approach with the latest technology allows for more adaptive, responsive and effective education.